Aboveground and belowground mammalian herbivores regulate the demography of deciduous woody species in conifer forests. Issue 10 (27th October 2016) - Endress, Bryan A.; Naylor, Bridgett J.; Pekin, Burak K.; Wisdom, Michael J.
Abstract: Mammalian herbivory can have profound impacts on plant population and community dynamics. However, our understanding of specific herbivore effects remains limited, even in regions with high densities of domestic and wild herbivores, such as the semiarid conifer forests of western North America. We conducted a seven‐year manipulative experiment to evaluate the effects of herbivory by two common ungulates, Cervus elaphus (Rocky Mountain elk) and cattle Bos taurus (domestic cattle) on growth and survival of two woody deciduous species, Populus trichocarpa (cottonwood) and Salix scouleriana (Scouler's willow) in postfire early‐successional forest stands. Additionally, we monitored belowground herbivory by Thomomys talpoides (pocket gopher) and explored effects of both aboveground and belowground herbivory on plant vital rates. Three, approximately 7 ha exclosures were constructed, and each was divided into 1‐ha plots. Seven herbivory treatments were then randomly assigned to the plots: three levels of herbivory (low, moderate, and high) for both cattle and elk, and one complete ungulate exclusion treatment. Treatments were implemented for seven years. Results showed that cattle and elk substantially reduced height and growth of both cottonwood and willow. Elk had a larger effect on growth and subsequent plant height than cattle, especially for cottonwood, and elk effects occurred even at low herbivore densities. Pocket gophers had a strong effect on survival of both plant species while herbivory by ungulates did not. However, we documented significant interaction effects of aboveground and belowground herbivory on survival. Our study is one of the first to evaluate top‐down regulation by multiple herbivore species at varying densities. Results suggest that traditional exclosure studies that treat herbivory as a binary factor (either present or absent) may not be sufficient to characterize top‐down regulation on plant demography. Rather, the strength of top‐down regulation varies depending on a number of factors including herbivore species, herbivore density, interactions among multiple herbivore species, and varying tolerance levels of different plant species to herbivory.